Tuhan Allah Impoten ? Kajian Kritis Terhadap Pengajaran Suhento Liauw - Lawolo, Mey Daman; Buaya , Nur Hayati (Sekolah Tinggi Teologi Sola Gratia Medan, 2024)
Abstract. According to the Bible, the purpose of the creation process is a statement about the existence and power of God. However, in Indonesia, there is Buddhism, which has the concept of God not as a creator, but a supreme state that is the purpose of life. As a non-theistic religion, it believes in the concept of the law of karma as a reference for living a life. This difference raises the question of whether the concept of God's predestination as proposed by John Calvin about God's absolute election from the beginning or a free will given by God to humans to respond to the salvation offered by God. The purpose of this study will bring understanding to Christians in evangelizing, preaching salvation to Buddhist groups. The methodology used is qualitative comparative analysis of each teaching. The conclusion is that every human being apparently seeks the ultimate goal of life which in Buddhism is called Nibbana and Christians identify as salvation. Nibbana can be achieved by the efforts of each individual by practicing the eightfold path of purity, and Christians can preach about Christ who gives the Helping Spirit, namely the Holy Spirit who will teach, remind, rebuke and give strength to be able to live life until reaching the final goal. Abstrak. Kedaulatan Allah merupakan topik yang sangat menarik dan telah memuat pro kontra yang tak kunjung berhenti menemukan titik temunya. Posisi kontranya seseorang terkait topik ini dilatarbelakangi dengan pemahaman manusia yang independen di hadapan Allah. Seperti yang diutarakan Suhento Liauw, dengan menjunjung tinggi kedaulatan Allah dan meminimalisir keberadaan manusia yang memiliki kebebasan maka hal itu merendahkan Allah dalam pengertian yang keliru. Bagi Suhento, setiap ajaran yang tidak mengakui kebebasan manusia dalam merespons kedaulatan Penciptanya, maka ajaran tersebut menghujat Allah dan menjadikanNya sebagai sosok yang kejam. Dengan menggunakan metode studi pustaka, kami menemukan bahwa pengajaran Suhento Liauw mengarah pada spirit atheism yang tidak berdasarkan kebenaran Alkitab. Sebaliknya, Alkitab menyatakan Allah yang berdaulat mengatur segala sesuatu yang dilakukan manusia, menentukan destinasi manusia oleh kehendakNya dengan disertai jaminan kekal yang ada di dalamnya. Sehingga, setiap orang yang telah mengenal kedaulatan Allah memperoleh kebahagiaan, ketentraman dan penghiburan yang abadi. Kedaulatan Allah tidak membatasi manusia berkreativitas di hadapanNya, melainkan mendorong manusia (umat pilihan) untuk berkarya bagi Allah demi keagungan dan kemuliaan-Nya.